Maternal SIN3A Regulates Reprogramming of Gene Expression During Mouse Preimplantation Development. Issue 4 (1st October 2015) - Jimenez, Richard; Melo, Eduardo O.; Davydenko, Olga; Ma, Jun; Mainigi, Monica; Franke, Vedran; Schultz, Richard M.
Abstract: The oocyte-to-embryo transition entails genome activation and a dramatic reprogramming of gene expression that is required for continued development. Superimposed on genome activation and reprogramming is development of a transcriptionally repressive state at the level of chromatin structure. Inducing global histone hyperacetylation relieves this repression and histone deacetylases 1 and 2 (HDAC1 and HDAC2) are involved in establishing the repressive state. Because SIN3A is an HDAC1/2-containing complex, we investigated whether it is involved in reprogramming gene expression during the course of genome activation. We find that Sin3a mRNA is recruited during maturation and that inhibiting its recruitment not only inhibits development beyond the 2-cell stage but also compromises the fidelity of reprogramming gene expression. The SIN3A that is synthesized during oocyte maturation reaches a maximum level in the mid-1-cell embryo and is essentially absent by the mid-2-cell stage. Overexpressing SIN3A in 1-cell embryos has no obvious effect on pre- and postimplantation development. These results provide a mechanism by which reprogramming can occur using a maternally inherited transcription machinery, namely, recruitment of mRNAs encoding transcription factors and chromatin remodelers, such as SIN3A.